1981
DOI: 10.1007/bf00423404
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and muscle enzyme adaptations to two different intensities of swim training

Abstract: To test the hypothesis that a smaller quantity of high intensity (HI) as opposed to a larger quantity of moderate intensity (MI) swim training would result in adaptations more specific to the short performance times of swimming competitions, two groups of elite university swimmers were tested before and after 6.5 weeks of specific HI or MI intermittent swim training. In training, swimming times were faster and blood lactate concentrations were higher (10.2 vs. 7.5 mM) during HI compared to MI training. No sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…However, it is doubtful if these athletes were completing each interval at a sprint intensity. A training study with swimmers also demonstrated similar increments in HAD and SDH enzyme activity through interval and continuous training (Houston et al 1981). Differences may have been apparent if either or both training regimens altered performance parameters like peak ,,"02 associated with tethered swimming.…”
Section: Oxidative Enzyme Response To Sprint Trainingmentioning
confidence: 70%
See 2 more Smart Citations
“…However, it is doubtful if these athletes were completing each interval at a sprint intensity. A training study with swimmers also demonstrated similar increments in HAD and SDH enzyme activity through interval and continuous training (Houston et al 1981). Differences may have been apparent if either or both training regimens altered performance parameters like peak ,,"02 associated with tethered swimming.…”
Section: Oxidative Enzyme Response To Sprint Trainingmentioning
confidence: 70%
“…The reverse was true for ST fibre area which increased significantly from month 2 to month 6. Swim training for 6.5 weeks by elite swimmers, while increasing relative area of FTa fibres, did not produce absolute changes in area (Houston et al 1981). Thus, there is conflicting evidence as to which fibres and the sequence in which fibres are hypertrophied by endurance training.…”
Section: Contractile Properties and Fibre Proportionmentioning
confidence: 78%
See 1 more Smart Citation
“…The systematic review by Nugent et al (2016) identified 4 HIT studies that were conducted on senior swimmers (Houston et al, 1981; Kame et al, 1990; Kilen et al, 2014; Termin and Pendergast, 2000). The studies ranged in duration from 6.5 weeks to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them focused their attention in a single domain (energetics or biomechanical one). According to the literature, significant improvements in maximal oxygen consumption (Magel et al 1975;Houston et al 1981;Termin and Pendergast 2000), velocity at 4 mmol L -1 of lactate levels (Reis and Alves 2006;Robertson et al 2010) and lactate tolerance (Sharp et al 1984;Pyne et al 2001) were observed due to the training process. Changes in the biomechanical variables were observed as well.…”
Section: Introductionmentioning
confidence: 94%